The boys start the war - Naylor(3, (BPhyllis Reynoldss (New York Delacorte Press, 1993)
Disgusted that a family with three girls moves into the house across the river, nine-year-old Wally and his three brothers declare a practical joke war on the girls
Hurg
5
Keywords: Brothers -- Fiction; Practical jokes -- Fiction